INTERNALISASI BUDAYA PESANTREN PADA KURIKULUM SEKOLAH - Muhammad Sya’roni (Fakultas Agama Islam Universitas Billfath, 2019)
The culture of pesantren is the work, feeling and creation of goods, regulations, ideas, activities, language, behavior, beliefs and habits in boarding schools that have been mutually agreed upon. Among the pesantren cultures that can be internalized in the school curriculum include the Deepening of the religious sciences; Mondok; Obedience; Exemplary; Piety; Independence; Discipline; Simplicity; Tolerance; Qana'ah; Humble; Fortitude; Solidarity / Please help; Sincerity; Istiqamah; Society; Cleanliness. The internalization of pesantren culture is integrated into all school activities, both intracurecular and extra-curricular activities.